(untitled) (Medical Forum Monthly, 2024)
Objective: We aim to share our experience of scaphoid fractures repair with screw and its impact on the outcome. Study Design: Retrospective case control study Place and Duration of Study: This study was conducted at the Plastic Surgery Department, Liaquat National Hospital, Karachi from January, 2011 to December, 2015 Materials and Methods: We retrieved and compared all patients meeting our inclusion criteria, who had undergone scaphoid fracture fixation with either lag screw or compression screw, and sorted them into two groups respectively. Post-operative time was noted and patient rated wrist evaluation (PRWE) was used to objectify pain and function. Results: Most of our patients were males 91.3% (21) with mean age of 26.4 ± 5.2 years.69.5% (16) of the patients were right hand dominant. Out of 23 fractures we managed 65.2% (15) with AO lag screws and 34.7% (8) with cannulated compression screws.The mean total PRWE score was 37.6. Eighty seven percent (20) of the patients showed improvement after intervention for scaphoid fractures, with PRWE mean pain score of 8.9. Conclusion: Early scaphoid fractures fixation using compression screws reduces operative time, pain and helps a young man to resume the earning in his productive years of life.